Case report: embryonal rhabdomyosarcoma in an English Bulldog - Rojas Hurtado, Jessenia Julieth (2017)
This paper describes the clinical case of a female English Bulldog canine, 10 months old, that was brought to consultation due to the presence of a superficial and accelerated growth node in the left abdominal area. The physical exam showed a sessile mass, approximately 2 x 3 cm, located on the skin of the left flank, close to the second mammary gland, and painless. The patient was subjected to an excisional biopsy to remove the entire mass. The histopathological study showed an embryonal rhabdomyosarcoma, a rare disease in dogs. The removal of the neoplasm was successful and without reported recurrence in the six months after its removal.